CANNING OF OIL SARDINE (SARDINELLA LONGICEPS)-NATURAL PACK - UNNIKRISHNAN NAIR, T S; MADHAVAN, P; BALACHANDRAN, K K; PRABHU, P V (Fishery Technology, 2017)
A simple and economic process for canning of oil sardine ( Sardinella longiceps) in its own juice having very good organoleptic characteristics has been developed. The process consists in dipping eviscerated, scaled and cleaned fish in brine containing potash alum and citric acid, packing in cans, exhausting and seaming without addition of any filling medium and heat processing. Â